2020
DOI: 10.1038/s41598-020-65158-y
|View full text |Cite|
|
Sign up to set email alerts
|

Reciprocal semantic predictions drive categorization of scene contexts and objects even when they are separate

Abstract: Visual categorization improves when object-context associations in scenes are semantically consistent, thus predictable from schemas stored in long-term memory. However, it is unclear whether this is due to differences in early perceptual processing, in matching of memory representations or in later stages of response selection. We tested these three concurrent explanations across five experiments. At each trial, participants had to categorize a scene context and an object briefly presented within the same ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 59 publications
(82 reference statements)
3
13
0
Order By: Relevance
“…Importantly, we also found less accurate classification of backgrounds when they comprised an incongruent object. We are aware of three previous studies in which a similar effect was found (Davenport and Potter, 2004;Davenport, 2007;Leroy et al, 2020). This observation is particularly important, as it seems to be at odds with the discussed theoretical models.…”
Section: Background Affects Object Recognition and Vice Versamentioning
confidence: 67%
See 2 more Smart Citations
“…Importantly, we also found less accurate classification of backgrounds when they comprised an incongruent object. We are aware of three previous studies in which a similar effect was found (Davenport and Potter, 2004;Davenport, 2007;Leroy et al, 2020). This observation is particularly important, as it seems to be at odds with the discussed theoretical models.…”
Section: Background Affects Object Recognition and Vice Versamentioning
confidence: 67%
“…This view is supported by computational work showing that influence of an incongruent object can be accounted for using scene statistics only (Mack and Palmeri, 2010). On the other hand, finding a congruence effect even when a scene and object are presented separately, in different screen locations, goes against this account and supports a semantic component (Leroy et al, 2020).…”
Section: Background Affects Object Recognition and Vice Versamentioning
confidence: 93%
See 1 more Smart Citation
“…than scenecongruent objects (or vice versa). Perhaps GANs could arrive at realistically looking incongruent stimuli more efficiently compared to editing the stimuli manually in Adobe Photoshop CS 9.0 [87] or staging actual incongruent scenes and photographing them [88]. SinGAN [42] can blend (foreign) objects and backgrounds (see also [89,90]).…”
Section: How Do Children and Adults Recognize The Materials Properties Of Objects Based On Visual Input?mentioning
confidence: 99%
“…Nevertheless, several studies have suggested that the rapid extraction of a scene's gist provides enough information to create a preliminary semantic template of the world, which can guide attention to areas of interest within the scene (e.g., [32,33]). Furthermore, grasping a scene's main theme can facilitate object recognition by pre-activating or priming associated objects embedded within the scene to a degree that is sufficient for their partial recognition (e.g., [34][35][36][37][38][39][40][41][42]; but see different views on this issue in [43][44][45]). Support for this approach comes mainly from studies examining the effects of scene recognition (e.g., a farm) on the processing of contextually consistent (e.g., a cow) or inconsistent objects (e.g., a vacuum cleaner) embedded in the scene.…”
Section: Processing Scene-object Associative Relationsmentioning
confidence: 99%